Classification of different type of seizure using machine learning approach - Low, Li Yian (2019)
The following Final Year Project gives an overview of the work done by the student for Classification of different types of seizures using machine learning approach, with different methods avaliable. The report consists of 6 chapters – Chapter 1: Objectives of the project and introduction of EEG backgrounds, Chapter 2: Pre-processing and seizure segments, Chapter 3: Feature Extraction methods and results, Chapter 4: Feature Selection and results, Chapter 5: Classification and final results, Chapter 6: Conclusion on the results, future work and reflection.